Komposisi Kimia, Degradasi Nutrien dan Produksi Gas Metana in Vitro Rumput Tropik yang Diawetkan dengan Metode Silase dan Hay - B Santoso; B Tj Hariadi (Faculty of Animal Science, Bogor Agricultural University, 2008)
Six grass species (Pennisetum purpureum, Pennisetum purpureophoides, Sorghum sudanense, Brachiaria brizantha, Imperata cylindrica, and Panicum maximum) were harvested at 49 days and preserved as silage or as hay. Samples of silage and hay were evaluated by an in vitro gas production and in vitro nutrient degradability. Total gas production at 24 and 48 h as well as CH4 were higher (P < 0.01) in silage than in hay. Brachiaria brizantha had the highest (P < 0.01) gas production compared to other species, whereas P. purpureum had the highest CH4 production (mM/g organic matter degraded). Dry matter (DM) and organic matter (OM) degradations were higher (P < 0.01) in silage than hay. When compared with hay, silage had higher (P < 0.01) ammonia-N concentration (20.3 vs. 10.6 mg/100 ml) and higher (P < 0.05) butyric acid concentration (7.9 vs. 7.0 mM). Non-fiber carbohydrate (NFC) and crude protein contents were positively correlated with gas production (r = 0.51; P < 0.05) and CH4 production (r = 0.64; P < 0.01) at 48 h of in vitro incubation. However total gas and CH4 productions were negatively correlated with neutral detergent fiber (NDF) content. There were positive correlation between DM (r = 0.90; P < 0.01), OM (r = 0.93; P < 0.01), and NDF (r = 0.84; P < 0.01) degradations and gas production. Key words: tropical grasses, methane, silage, hay